Indoor air purification using heterogeneous photocatalytic oxidation - Han, Zhenan (2013)
Heterogeneous photocatalytic oxidation (PCO) is a very promising technology for mineralization of gaseous contaminants such as formaldehyde and other volatile organic compounds (VOCs) existing in the typical indoor environment. Current problems encountered when implementing PCO for indoor air purification include ineffective immobilization, low degradation efficiency and lack of UV light source indoors. This project experimentally investigated the photocatalyst immobilization method as well as visible-light induced PCO of gaseous formaldehyde. An easy and cost-effective spray-coating method was established through optimizing the substrate material, stabilization temperature, binder types and binder dosages. The effects from different limiting factors for the visible-light PCO reaction, such as volumetric flow rate, contaminant initial concentration, relative humidity, visible light intensity and photocatalyst loading amount, were carefully tested in a fix-bed PCO reaction system. The possible mechanisms of visible-light PCO of gaseous formaldehyde were explored by using two visible-light active photocatalysts and comparing between UV-PCO and visible-light PCO processes. A prototype indoor air cleaner equipped with visible-light PCO component was designed based on the scientific findings of the lab scale experiment. Its cleaning effectiveness was evaluated through environmental chamber test. The result shows considerable removal efficiency for both formaldehyde and other existing VOCs such as toluene. Relatively high clean air delivery rate (CADR), in comparing with other commercialized PCO air cleaners, was achieved for gaseous contaminants indoors with energy-efficient LED light source. This study provides a better understanding of visible-light induced PCO of gaseous contaminants, which might be used for design and preparation of high-performance indoor air cleaning devices. The spray-coating method is effective, economical and can be easily applied for large-scale photocatalyst immobilization.